Course assessment for skill transfer: A framework for evaluating skill transfer in online courses - Fischer, Heather A.; Preston, Kimberley; Staus, Nancy; Storksdieck, Martin (Frontiers in Education, 2022)
Science, technology, engineering, and mathematics (STEM) occupations are projected to grow over two times faster than the total for all occupations in the next decade. This will require reskilling and upskilling those currently in the workforce. In response, many universities are deliberately developing academic programs, and individual courses focused on providing relevant skills that can be transferred to the workplace. In turn, developers of such programs and courses need ways to assess how well the skills taught in their courses translate to the workforce. Our framework, Course Assessment for Skill Transfer (CAST), is a suite of conceptual tools intended to aid course designers, instructors, or external evaluators in assessing which essential skills are being taught and to what extent. The overarching aim of the framework is to support skills transfer from the classroom to the workplace. This paper introduces the framework and provides two illustrative examples for applying the framework. The examples show that the framework offers a customizable structure for course facilitators and evaluators to assess the skills taught, learned, and retained based on their needs and the resources available to evaluate the quality and usefulness of course offerings in higher education.